2018
DOI: 10.5091/plecevo.2018.1389
|View full text |Cite
|
Sign up to set email alerts
|

Stem anatomy at various developmental stages of secondary growth in Turbina corymbosa (Convolvulaceae)

Abstract: Background – Population growth of lianas in the tropical forest is credited to their ability of CO2 sequestration and efficiency of the narrow stems to supply water required for the amount of foliage it bears. Turbina corymbosa (L.) Raf. (Convolvulaceae Juss.) is one of the fast-growing invasive species of scrambling woody lianas. It covers trees entirely within a short period to compete with above-ground resources (particularly sunlight). However, no information is available on how it manages to cope up with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…Formation of intraxylary phloem is universal in Convolvulaceae and in most of the members, internal cambium initiates at the pith margin i.e. centrifugally to the intraxylary phloem (8,(11)(12)(13)17,18,25,26,31). In the present study, also observed periclinal divisions at the marginal pith cells between protoxylem and intraxylary phloem and results into a weak cambium (i.e.…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…Formation of intraxylary phloem is universal in Convolvulaceae and in most of the members, internal cambium initiates at the pith margin i.e. centrifugally to the intraxylary phloem (8,(11)(12)(13)17,18,25,26,31). In the present study, also observed periclinal divisions at the marginal pith cells between protoxylem and intraxylary phloem and results into a weak cambium (i.e.…”
Section: Discussionsupporting
confidence: 73%
“…Though, these features are common in most of the species of the family, formation of successive cambia lack in members viz., Convolvulus, Cressa and Wilsonia. On the other hand, occurrence of intraxylary/medullary/internal phloem is constant feature in all the members of the family studied so far (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). In the present study, Argyreia nervosa (Burm.…”
Section: Discussionmentioning
confidence: 49%
See 3 more Smart Citations